Impact of the health emergency on dairy and egg consumption in the Riobamba canton - Gavilánez Álvarez, Oscar Danilo (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020, 2021)
At present, the outbreak of the new coronavirus disease (COVID-19) has already caused a high cost in human lives, the coronavirus pandemic identified by COVID-19 has caused a marked instability in human survival, becoming the global emergency more pressing in the course of the last century as the virus spreads the economic impact (economic crisis) in Ecuador has radicalized, in all social sectors, from the point of view of sustainable economy, the great problem of consumption It is based on the fact that a large part of the population does not produce, but does consume, it is necessary to create a system that normalizes this situation and that helps each consumer to assign them some type of productive role, however small it may be. It is in this context, the present research aims to evaluate the impact of the health emergency on the consumption of dairy and eggs in the Riobamba canton, the behavior of the demand was determined, gathering primary information on the existing target market in the capital of Chimborazo province. The development of the research is based on the quantitative approach, at the explanatory level, in the observational, documentary, retrospective and transversal types. The method was inductive when observing the consumption made. The results of the research identify the impact of the health emergency on dairy and egg consumption in the Riobamba canton.